Casual perceptions of the inter-trait relations the glue that hold person types together Sedikides and Craig A. Anderson. - Sedikides, Constantine; Anderson, Craig
Two experiments tested the hypothesis that implicit personality theory person types are composed of casually interconnected traits. Experiment 1 showed that the weakest trait member of a person type is perceived as more casually related to the core trait members of the type than are nonmember traits, even when those non-member traits are both more highly-correlated with and closer in multidimensional scaling space to the core members that the weakest member.